Extremely fast synthesis of polythioether based phase change materials (PCMs) for thermal energy storage. (5th May 2020) - Daglar, Ozgun; Çakmakçı, Emrah; Hizal, Gurkan; Tunca, Umit; Durmaz, Hakan
Graphical abstract: Highlights: Long alkyl groups tethered polythioethers were synthesized. TBD catalyzed alkyne-thiol polymerization method was utilized. Polythioethers were synthesized within 1 min in excellent yields (71–99%). Polythioethers displayed good PCM properties with good thermal reliability. Docosanol based polythioethers were found to be superior with a ΔHm of 68.76 J/g. Abstract: Phase change materials (PCMs) are smart systems for thermal energy storage. In this study, we prepared long alkyl groups tethered polythioethers in the blink of an eye from diesters of acetylenedicarboxylic acid with fatty alcohols (lauryl alcohol, stearyl alcohol or docosanol) and various dithiols by using a 1, 5, 7-triazabicyclo[4.4.0]dec-5-ene (TBD) catalyzed alkyne-thiol polymerization which is a straightforward and extremely rapid method. All polymers were obtained in excellent yields (71–99%). All monomers and polymers were characterized by NMR and FTIR spectroscopies and the molecular weights of the polymers were determined by GPC. The weight average molecular weights ( M w ) of these polymers were found to change between 13.3 and 167.3 kDa. Phase change properties of these polythioethers were characterized by DSC and the thermal stability of the polymers were determined by TGA. The thermal reliability after 20 successive heating and melting cycles were also determined. According to our results, polymers prepared from docosanol based acetylenedicarboxylate monomer and 1, 4-benzenedimethanethiol were found to be superior. The heat of the melting of this polymer was found as 68.76 J/g and decreased to 67.28 J/g after 20 cycles. The T m and the T c of this polythioether were found as 56.44 °C and 47.75 °C, respectively.